2019
DOI: 10.1503/cmaj.181426
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pediatric emergency department crowding on patient and health care system outcomes: a multicentre cohort study

Abstract: E mergency department overcrowding is a complex systems problem and an important health services and public health concern. Although the magnitude of emergency department overcrowding varies regionally, the Canadian Association of Emergency Physicians has identified overcrowding as a serious problem across Canada, particularly at trauma and tertiary care centres. 1 In North America, emergency department overcrowding has been associated with reduced quality of care, negative clinical outcomes (mortality and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
(29 reference statements)
0
39
1
2
Order By: Relevance
“… 1 , 2 To address this threat to patient safety and quality of care, researchers have attempted to investigate the causes of crowding in adult and pediatric EDs, 3 proposed solutions to solve the problem, 4 - 6 studied safety concerns associated with crowding, 7 - 9 and analyzed the impact of crowding. 7 , 10 , 11 Research on this topic also has tried to establish an association between ED crowding and the quality of care provided to ED patients. 12 , 13 Despite a significant body of research on this topic, there remains no standard definition or measurement of ED crowding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 To address this threat to patient safety and quality of care, researchers have attempted to investigate the causes of crowding in adult and pediatric EDs, 3 proposed solutions to solve the problem, 4 - 6 studied safety concerns associated with crowding, 7 - 9 and analyzed the impact of crowding. 7 , 10 , 11 Research on this topic also has tried to establish an association between ED crowding and the quality of care provided to ED patients. 12 , 13 Despite a significant body of research on this topic, there remains no standard definition or measurement of ED crowding.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency department (ED) crowding is a global public health problem which probably will worsen as ED visits increase in many countries. 1,2 To address this threat to patient safety and quality of care, researchers have attempted to investigate the causes of crowding in adult and pediatric EDs, 3 proposed solutions to solve the problem, [4][5][6] studied safety concerns associated with crowding, [7][8][9] and analyzed the impact of crowding. 7,10,11 Research on this topic also has tried to establish an association between ED crowding and the quality of care provided to ED patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 The overcrowding of EDs has been shown to contribute to additional mortality overall, 4 while in paediatric services (which generally have a very low mortality) it has been shown to increase the rate of hospital admission and representations within the following week. 5 One of the many strategies that has been proposed to counter this phenomenon is the diversion of lowurgency patients to general practice, despite the evidence that these patients use very few ED resources 6 and the real cause of overcrowding is actually insufficient numbers of inpatient beds. 7 A recent systematic review found no evidence for success of these diversion strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A linked study provides evidence that overcrowding in Canadian pediatric emergency departments negatively affects the care of both those triaged as requiring urgent care and those requiring less urgent care, by an increased rate of hospital admission and an increased rate of reattendance after discharge, respectively. 1 Doan and colleagues conducted a retrospective cohort study looking at more than 1.9 million attendances to 8 Canadian pediatric emergency departments over 5 years to determine whether overcrowding in the emergency department is associated with adverse outcomes -defined as hospital admission at the index visit, return to the department or hospital admission within 7 days of discharge from the emergency department, and mortality within 14 days.…”
mentioning
confidence: 99%
“…11 The authors of the linked study found that overcrowding may adversely affect care that children received, with patients triaged to the least urgent categories (CTAS 4 and 5) more likely to return within 7 days. 1 This may reflect an unsatisfactory initial visit for the least urgent patients, which may be a result of differing expectations between the parents and the emergency department clinician or emergency departments being poorly set up to meet the needs of these patients.…”
mentioning
confidence: 99%